(untitled) (The Journal of the International Society of Chinese Health Practices, 2021)
This paper discusses the current status and evolution path of Chinese literature. This paper retrieved 1343 Taijiquan related documents including CSSCI, CSCD in CNKI database and Peking University, and used the CNKI database to visually analyze the research topics, author, organization distribution, research network structure and evolution characteristics of Taijiquan, aiming to explore the dynamic trend and characteristics of Taijiquan research and provide theoretical data exploration for the further development of Taijiquan. The research shows that the number of Taijiquan fluctuates on the whole; the research institutions are mainly distributed in universities and low cooperation frequency can be further improved; the research is mainly focused on Taijiquan, the regulation of bone density and quality of life. Objective: To explore the dynamic trend and characteristics of Taijiquan in China and provide theoretical data for the further development of Taijiquan. Methods: As a traditional national sport project, Taijiquan has the role of cultural communication. In order to explore Taijiquan research hotspot, the author on the knowledge network search "taichi", search time on April 6, 2021, the latest data update date is April 15, 2021, through CNKI, using CiteSpace visual analysis tools for Taijiquan literature analysis, on the basis of quantitative and qualitative combination, to map taichi research knowledge map, clear the forefront of Taijiquan research, expounds the relevant content of domestic taichi research authors, interpret the evolution path of taichi research field. Results: The movement of Taijiquan research in China originated in the Ming and Qing Dynasties and experienced a long period of development. It developed after the founding of the Republic of China and the New Republic of China. Deep academic research on Taijiquan began in the 1990s. In the stage of rapid development (2000-2010), Taijiquan was included in the list of the first batch of national intangible cultural heritage in China. China’s successful bid and Olympic Games played a great role in promoting sports, and Taijiquan was further developed. During the fluctuation development stage (2010-2020), the research structure has changed and the number of documents fell somewhat, but the research attention is still very high. The hot spots of domestic scholars on Taijiquan are constantly changing. In terms of Taijiquan culture, from the study of philosophy of Taijiquan to the inheritance and innovation of traditional culture, the research perspective has been constantly expanding, and the research is multi-dimensional. The research of Taijiquan is becoming more and more detailed, manifested in the embodiment of the research subjects, from middle-aged and elderly to middle-aged women, and cross-aged research at different aged stages, including young women. The practical improvement of research content is not only for the simplification and study of action content, but also for the prevention and treatment of disease, and to assist in the ability improvement of other specialties. Research means are scientific, and the degree of data analysis is improved. The number of Taijiquan issued showed a fluctuating growth trend, falling highly after 2016. The main strength in the field of Taijiquan is concentrated in professional sports colleges and comprehensive and normal universities. The hot spots of Taijiquan research are Taijiquan, Taijiquan, Wushu and Wang Zongyue, and with these hot topics to conduct Taijiquan, Taijiquan teaching, Taijiquan culture and other topics. Taijiquan sports research group is mainly concentrated in middle-aged and elderly, focusing on middle-aged and elderly women and elderly men. Follow the study to improve the quality of survival, such as improving bone density and cardiopulmonary function, as well as exercise treatment and scientific monitoring of chronic diseases. The change of the research theme is divided by 2010, gradually transforming from Taijiquan to the research on the health promotion of Taijiquan. Key researchers in the field of Taijiquan, Jiang Juan, Yu Dinghai, Yang Jianying, there are cooperation relationship, but the cooperation between other research scholars is less, mainly to the institution, cooperation and exchanges between research institutions is not close, can further expand the cooperation space, strengthen interdisciplinary exchanges, common research between projects, give full play to the complementary advantages of human resources. The goals and requirements to improve the quality of survival through Taijiquan will continue, Therefore, increase communication between disciplines, conduct scientific research, and effectively make the physical function of the masses to improve and help. Build a comprehensive research mechanism, actively explore the implementation path of the development of Taijiquan, and promote innovative research. Conclusion: The volume of Taijiquan fluctuates on the whole; Taijiquan research institutions are mainly distributed in universities with low cooperation frequency and can be further improved; Taijiquan is mainly focused on the regulation of bone density and quality of life.